Decompressive craniectomy versus conservative treatment: limits and possibilities in malignant stroke - MAIA, Isaac Holanda Mendes; MELO, Thaissa Pinto de; LIMA, Fabrício Oliveira; CARVALHO, João José de Freitas; MONT’ALVERNE, Francisco José Arruda; LOPES, Edson, JÚNIOR; DIÓGENES, Marcelo Bezerra; CUNHA, Thaís Saraiva Leão; QUEIROZ, Bárbara Matos Almeida; TAMIETTI, Marina Franciss; MAIA, Fernanda Martins (Arquivos de Neuro-Psiquiatria, 2020)
Background: Malignant infarction of the middle cerebral artery (MCA) occurs in a subgroup of patients with ischemic stroke and early decompressive craniectomy (DC) is one of its treatments. Objective: To investigate the functional outcome of patients with malignant ischemic stroke treated with decompressive craniectomy at a neurological emergency center in Northeastern Brazil. Methods: Prospective cohort study, in which 25 patients were divided into two groups: those undergoing surgical treatment with DC and those who continued to receive standard conservative treatment (CT). Functionality was assessed using the modified Rankin Scale (mRS), at follow-up after six months. Results: A favorable outcome (mRS≤3) was observed in 37.5% of the DC patients and 29.4% of CT patients (p=0.42). Fewer patients who underwent surgical treatment died (25%), compared to those treated conservatively (52.8%); however, with no statistical significance. Nonetheless, the proportion of patients with moderate to severe disability (mRS 4–5) was higher in the surgical group (37.5%) than in the non-surgical group (17.7%). Conclusion: In absolute values, superiority in the effectiveness of DC over CT was perceived, showing that the reduction in mortality was at the expense of increased disability.
Keywords: stroke; brain edema; decompressive craniectomy